The Portrait of Emigrant in Citizen Journalism - Pakėnaitė, Agnė (Žurnalistikos tyrimai, 2017)
The object of the paper is citizen journalism platforms of online media outlets “Pilietis” (Delfi.lt) and “Bendraukime” (Lrytas.lt) 2012–2014. Work aim is to find how emigration topic is covered in citizen journalism and what portrait of emigrant is framed by citizens’ authors. Work tasks: research emigration problem in Lithuania; analyze the newest statistics of emigration from Lithuania; find the main reasons of emigration from Lithuania; research process of citizen journalism; investigate articles about emigration in online media outlets Delfi.lt and Lrytas.lt citizen journalism platforms. Having analyzed academic literature and researched publications of citizen journalism platforms in online media outlets, it was concluded that emigration topic in citizen journalism is discussed a lot. Authors are both: emigrants and inhabitants in Lithuania. The most active authors are emigrants. Usually they chose emigration because of economic reasons. They are covering emigration in a positive way, but criticize Lithuania. The portrait of emigrant in citizen journalism is “emigrant worker”. Inhabitants are also participating in citizen journalism. They differently from emigrants share their negative opinions about emigration process. Citizen journalism platforms make even bigger opportunities to spread conflict between emigrants and Lithuanians, who are against emigration.